LEAN CONSTRUCTION IN THE PLANNING AND CONTROL OF MINHA CASA MINHA VIDA PROJECTS - Losito, Thiago Komoto (Seven Editora, 2025)
The Brazilian construction sector has been facing a recession since 2014, peaking in 2016 with a negative growth rate of 10% and closing 2018 with a negative variation of 2.5% (CBIC, 2018). Given this scenario, coupled with high waste rates and low productivity, production management and control are essential to ensure economic competition, rapid response to opportunities and customers, cost reduction, and increased productivity (Ellis and Lange, 1994). Against this backdrop, this study aimed to identify and present Lean Construction practices in a vertical social housing condominium project financed by the Federal Government's Minha Casa Minha Vida program in Ferraz de Vasconcelos, São Paulo, Brazil. The project analysis was conducted through site visits and a questionnaire developed based on Carvalho (2008), Neves (2010), and Arantes (2008). In conjunction with field verification, the project plan was developed using the Percentage of Completed Planning (PPC), Line of Balance (LDB), and Last Planner System (LPS) tools, adopted in the lean philosophy. These tools allow for analyzing the macro flow and scheduling input purchases in advance to avoid inventory buildup and delays due to lack of materials. This reduces the project schedule by 16% and waste by 18%. This also highlights the opportunity for applying this concept due to the significant interest among professionals in the topic.DOI: https://doi.org/10.56238/sevened2025.029-114